Age-related ranges of respiratory inductance plethysmography (RIP) reference values for infants and children. (February 2019) - Balasubramaniam, Sona Lakshme; Wang, Yanping; Ryan, Lauren; Hossain, Jobayer; Rahman, Tariq; Shaffer, Thomas H.
Summary: The current noninvasive method for respiratory monitoring is respiratory inductance plethysmography (RIP); two bands are connected, one each to the chest and the abdomen, to measure the breathing pattern. RIP requires post hoc analysis to calculate indices such as respiratory rate, phase angle, labored breathing index, and percent of rib cage contribution to breathing. Clinical studies have provided patient RIP values and age-matched normal values, but they lack global evaluation of normative data for a wide age range of pediatric subjects. Herein, we compiled normative RIP indices from numerous studies for a large range of pediatric ages. From these data, we derived regression equations useful for computing normal RIP parameters as a function of age. The presented review will provide caregivers the ability to compare RIP data of pediatric patients against the regression analysis. This comparison will help identify patients with pulmonary complications and aid in guiding respiratory therapy.